(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
In this article, the STEAM and STEM education systems, the creation of a STEAM education system, the influence of STEAM and STEM education systems on the effectiveness of education, the main goals and objectives of the STEAM educational program, STEAM in the education of children of primary school age. The role of the system modules and the basic pedagogical principles in organizing the STEAM educational program in schools are discussed.